Microfinance Meets the Market - Cull, Robert; Demirgüç-Kunt, Asli; Morduch, Jonathan (World Bank, Washington, DC, 2012)
Microfinance institutions have proved the possibility of providing reliable banking services to poor customers. Their second aim is to do so in a commercially-viable way. This paper analyzes the tensions and opportunities of microfinance as it embraces the market, drawing on a data set that includes 346 of the world's leading microfinance institutions and covers nearly 18 million active borrowers. The data show remarkable successes in maintaining high rates of loan repayment, but the data also suggest that profit-maximizing investors would have limited interest in most of the institutions that are focusing on the poorest customers and women. Those institutions, as a group, charge their customers the highest fees in the sample but also face particularly high transaction costs, in part due to small transaction sizes. Innovations to overcome the well-known problems of asymmetric information in financial markets were a triumph, but further innovation is needed to overcome the challenges of high costs.